2011
DOI: 10.1007/s11207-011-9747-0
|View full text |Cite
|
Sign up to set email alerts
|

Ionospheric Day-to-Day Variability Around the Whole Heliosphere Interval in 2008

Abstract: Ionospheric F2 peak electron densities (NmF2) measured at ten ionosonde stations have been analyzed to investigate ionospheric day-to-day variability around the Whole Heliosphere Interval (WHI) in 2008 (Day of Year (DOY) 50 -140). The ionosonde data showed that there was significant global day-to-day variability in NmF2. This variability had 5-, 7-, 9-, 11-, 13.5-, and 16 -21-day periodicities. At middle latitudes, the ionosphere appeared to respond directly to the solar-wind and interplanetary-magnetic-field … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
68
0

Year Published

2011
2011
2014
2014

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 45 publications
(70 citation statements)
references
References 49 publications
2
68
0
Order By: Relevance
“…The ionosphere and thermosphere respond most strongly to negative IMF B Z , where the periodicity in B Z was mostly around 27, and 13.5 days, with a significant peak at seven days. Wang et al (2011) found that the periodicities in B TOT and B Z for three Carrington rotations centered around CR 2068/WHI were similar to those for the entire year. Most of the parameters in Figure 11 share the nine-day periodicity of the solar wind, including the peak electron density in the F region (NmF2) at all latitudes studied by Wang et al (2011).…”
Section: The Response At Geospacementioning
confidence: 61%
See 4 more Smart Citations
“…The ionosphere and thermosphere respond most strongly to negative IMF B Z , where the periodicity in B Z was mostly around 27, and 13.5 days, with a significant peak at seven days. Wang et al (2011) found that the periodicities in B TOT and B Z for three Carrington rotations centered around CR 2068/WHI were similar to those for the entire year. Most of the parameters in Figure 11 share the nine-day periodicity of the solar wind, including the peak electron density in the F region (NmF2) at all latitudes studied by Wang et al (2011).…”
Section: The Response At Geospacementioning
confidence: 61%
“…showed that the geomagnetic indices of the auroral electroject (AE) and the disturbed (Dst) equatorial current were larger for the first HSS than for the second. Wang et al (2011) showed that Kp and the ionospheric-storm responses were larger for the first HSS than for the second. Indeed, increased responses for negative IMF GSM B Z can be seen in the larger responses in the geospace parameters in Figure 11 between the red vertical lines marking the HCS crossings.…”
Section: The Response At Geospacementioning
confidence: 95%
See 3 more Smart Citations